Compliance analysis of sentence structure ensures that sentences are clear and easy to read. Proper sentence structure helps convey the intended meaning without ambiguity, making the text more comprehensible to readers. - -, Bagus Setyadi; Rina Octaria (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to explore the impact of the level of analytical compliance on sentence structure in a text. Analytical compliance refers to the extent to which a system or method can understand and follow grammatical and syntactic rules in a particular language. Using a computational linguistics approach, this research analyzes how the level of analytical compliance can influence understanding and sentence structure in a text. This discovery has important implications in the development of natural language processing technology, especially in improving the system's ability to understand and produce sentences that conform to language norms. Increasing analytical compliance is expected to improve the quality of communication and overall understanding of text content. This research contributes to our understanding of the role of analytical compliance in shaping sentence structure in the context of computational linguistics.